Pelatihan Pembuatan Video Dokumentasi Kegiatan Tahunan dan Kegiatan Bidang di Dinas Sosial Kabupaten Lombok Tengah Menggunakan Aplikasi CapCut - Juli Muslim Ihsan; Muhammad Fauzi Zulkarnaen (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The implementation of this service aims to improve the skills of employees of the Social Service of Central Lombok Regency in making video documentation of annual activities and field activities using the CapCut application. using the CapCut application. Effective video documentation is the main need in conveying information and activity reports to the community and stakeholders. This training was designed in several stages, namely identification of needs, module development, implementation of theoretical and practical training, and evaluation of participants' skills through the pre-test and post-test. The results of the activity showed a significant increase in significant improvement in participants' skills, especially in the aspects of video editing, use of transition features and visual effects, and systematic narration. systematic narration. The impact of this training is expected to improve efficiency in the documentation process, reduce reliance on external services, and strengthen the transparency and accountability of the Social Affairs Office, as well as strengthen the transparency and accountability of the Central Lombok Regency in delivering information to the public.